Relationship Between Microplastics Abundance and Sediment Organic Content in Dumai Coastal Waters - Zientika, Zientika; Amin, Bintal; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
Plastics in the environment would eventually be degraded into plastic granules which are called microplastics. In recent years, microplastics have been spread widely not only inland but also in aquatic habitats, where averagely 5% of the plastic produced each year will end up in marine waters. The purpose of this study which was conducted in October to November 2020 was to identify the type and abundance of microplastics in the sediment as well as its possible relationship with the sediment organic matter in Dumai waters. Sediment samples were taken from Dumai coastal waters by using purposive sampling method. Identification of the types and abundance of microplastics as well as the analysis of sediment organic content were carried out in the Laboratory of Chemical Oceanography, Department of Marine Sciences, Universitas Riau. Microplastic and sediment particles were separated using 150 ml saturated NaCl solution. The types of microplastics found are fiber, fragment and films, where fiber was found to be the most commonly found (36.43%), followed by fragments (31.97%) and films (31.60%), respectively. No significant correlation found between microplastic abundance and the sediment organic content in Dumai coastal waters.